Prevalence of Seed-Borne Fungi Associated With Selected Rice Varieties of Brri (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Selected rice varieties such as BR-78, 80, 81, 82, 83, 84, 86, 87, 88 and 89 were used in this experiment to investigate the prevalence of seed-borne fungi. A total of twelve fungi belonging to six genera was isolated from the seeds of selected BRRI (Bangladesh Rice Research Institute) rice varieties by using tissue planting method. They were Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tieghem, A. ochraceous Wilhelm, A. terreus Thom, Curvularia lunaata (Wakker) Boedijn, Curvularia sp. 1, Drechslera oryzae Breda de Haan (Subramanian and Jain), Penicillium sp.1, Penicillium sp. 2 and Rhizopus stolonifera (Ehrenb.) Vuill., Among the isolated fungi A. niger was the most prevalent fungi associated with the seeds of the rice varieties with a mean per cent frequency of 16.93 and the least prevalent fungi was A. ochraceous with a mean per cent frequency of 0.27. Mean per cent frequency of A. niger (16.33) was highest which was followed by A. flavus (7.27), Penicillium sp.1 (5.93), Penicillium sp. 2 (3.27), Drechslera oryzae (2.67) and A. terreus (2.53). Among the identified seed-borne fungi Curvularia lunata and Drechslera oryzae were found as pathogenic and cause seed-borne diseases.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 61-68